‘No one cares about the animal like me.’ Indian veterinarians’ experiences of improving animal welfare through Continuing Professional Development - Emma L Rayner; Ranjita Bastola; Sumanth Bedre; Andrew D Gibson; Luke Gamble; Jill RD MacKay (Animal Welfare)
Veterinarians are custodians of animal welfare, ensuring practices remain current and effective in the face of the ever-changing demands of the profession. Continuing Professional Development (CPD) is essential for protecting animal welfare, however access to quality CPD is a challenge in many countries. India has one of the fastest growing veterinary industries globally, emphasising the importance of accessible CPD opportunities that are relevant to this setting. This study used focus groups to explore how Indian veterinarians identify relevant CPD, barriers they encounter, and their experiences with CPD. We describe three themes: (1) ‘career vs calling’, where veterinarians’ extrinsic and intrinsic motivational factors were identified, such as their desire to protect animal welfare; (2) being ‘willing to learn but can’t’, with context-specific barriers, such as accessing reliable CPD information; and (3) ‘real interactions matter’, where participants described how pedagogical design influenced their choices, e.g. being able to observe animal welfare improvements through practical teaching. We have three recommendations: firstly, to improve CPD learning opportunities informed by evidence-based methods, to meet knowledge and skills gaps such as the high demand for practically focused training; secondly, the development of a unified accreditation and quality assurance framework to assess content, relevance and delivery standards of available CPD options to veterinarians; and, lastly, improved support from employers to address current barriers and facilitate attendance. These findings contribute to the current knowledge gap of factors that influence Indian veterinarians’ experiences of attaining relevant, accessible CPD and makes suggestions to improve standards of veterinary care and, ultimately, patient welfare.